THE ROLE OF EDUCATIONAL TOOLS IN IMPROVING ARABIC LANGUAGE SKILLS AMONG STUDENTS AT THE NOURI EDUCATIONAL INSTITUTION – DAR AL-MADANI SCHOOL – NORTH SUMATRA - Hasibuan, Jamaluddin; S, Fahrurrozi. (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This lesson addresses the role of teaching methods in improving students' Arabic language skills at Al-Anwar Educational Institution and Dar Al-Madani School. The study aims to determine how teaching methods improve students' Arabic language skills and how the use of teaching methods improves students' Arabic language skills. This study relied on a qualitative descriptive approach. The study used primary and secondary data. The study was conducted at Al-Anwar Educational Institution and Dar Al-Madani School. The results of the study showed that educational tools can improve students' Arabic language learning skills. This was obtained by observing the activities carried out by students in the classroom during the teaching process and through the results of daily assessment tests for students after the teaching process. Teachers at Al-Anwar Educational Institution and Dar Al-Madani School use teaching aids such as blackboards, pictures, word cards, objects inside and outside the classroom, and textbooks. The support tools provided by the school are projectors (Infocus) to improve the Arabic language skills of students at Al-Anwar Educational Institution and Dar Al-Madani School.